CHEMICAL COMPOSITION AND ATMOSPHERE PARAMETERS OF THE DOUBLE-MODE CEPHEID U TRA - Usenko, I. A.; Knyazev, A. Yu.; Berdnikov, L. N.; Kravtsov, V. V. (Одеські астрономічні публікації, 2013)
Four high-resolution spectra of the doble-mode Cepheid UTrA have been obtained during its pulsational period. For the ﬁrst time, we obtained accurate atmosphere parameters and the chemical abundance of a number of elements, in particular of sodium, magnesium, and aluminium. We estimated the mean Teﬀ =608529K, logg=2.000.15, and Vt =3.900.25kms 1. A deﬁcit of carbon ([C=H] =–0.350.23dex), over abundance of both sodium ([Na=H]=+0.150.25dex) and aluminium ([Al=H] =+0.300.32dex) are typical for Cepheids passing through the ﬁrst dredge-upphase. The abundance of iron ([Fe=H]=+0.010.15dex) is very close to the solar one. Moreover, we ﬁnd that -elements, those of Fe-group, as well as ”light” - and ”heavy”-, s- and r- process elements, all of them have abundances close to solar values, too, excepting may be severale lements with slight enhance or deﬁcit.